Peningkatan Kesehatan dengan Pendampingan Kegiatan Terapi Aktivitas Kelompok pada Lansia - Fitri Anggraeni; Luluk Eka Meylawati; Harwina Widya Astuti (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Elderly health needs special attention so that it not only helps the elderly live longer, but also can enjoy old age happily and improve their quality of life. The growth of the elderly population has a significant impact on many aspects of life. The impact of globalization has also caused family values ​​and roles to change. As a result of changes in family composition, families view the presence of the elderly in the family environment as a burden. So that more and more families choose to leave the elderly in nursing homes rather than living with family members to care for them. The purpose of this activity is to improve the health of the elderly at PSTW Budi Mulia I by implementing group activity therapy. The group activity therapy method is carried out systematically through four stages, namely pre-interaction, orientation, work, and termination. Based on the results of community service from 45 elderly people for verbal ability, 36 elderly people (80%) were able to answer 3 pictures correctly, 5 elderly people (11.1%) were able to answer 2 pictures correctly, and 4 elderly people (8.9%) were able to answer 1 picture correctly. Keywords: Keywords: Elderly ; Group Activity Therapy.